Use of Expedited Partner Therapy for Sexually Transmitted Diseases in College and University Health Centers in the United States, 2011–2012. Issue 10 (October 2015) - Cramer, Ryan; Martinez, Nina; Roberts, Craig; Habel, Melissa A.; Leino, E. Victor; Leichliter, Jami S.
Abstract : Abstract: We examined expedited partner therapy for chlamydia and gonorrhea in college and university health centers by institutional and policy characteristics. Expedited partner therapy awareness and use was low (44.1% used), did not differ by institutional characteristics, and differed by policy environment. Our findings suggest missed opportunities for sexually transmitted disease prevention in college and university health centers. Abstract : Expedited partner therapy awareness and use in college and university health centers is low, does not differ by institutional characteristics, and differs by policy environment. Missed sexually transmitted disease prevention opportunities may exist in college and university health centers.